2010
DOI: 10.2306/scienceasia1513-1874.2010.36.286
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study was designed to determine the anthocyanin cyanidin-3-glucoside content and antioxidant activity of rice varieties under salinity stress. Two classes of Thai rice lines: cyanic (Riceberry, Kham, and Khamdoisaket) and acyanic (KDML 105, Sinlek, were hydroponically grown. Seedlings were grown for 16 days and were supplied with salinity nutrient solution with 0 (control) and 60 mM NaCl for 11 days. The total phenolic content and the antioxidant activity, including 2,2-diphenyl-1-picrylhydrazyl free radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 28 publications
1
19
1
Order By: Relevance
“…Likewise, The α-glucosidase inhibiting property of phenolics, anthocyanins, GABA, and tocols was increased from 64.28 ± 2.51, 64.42 ± 2.70, 63.10 ± 1.71, and 63.62 ± 1.35 to 81.44 ± 2.05, 80.84 ± 2.23, 76.40 ± 2.01, and 76.59 ± 1.33% of inhibition/mg of extracts, respectively ( Figure 3A (b)). The germination improved the free radical scavenging ability of several Thai rice varieties (Daiponmak et al, 2010;Chutipaijit et al, 2009Chutipaijit et al, , 2011Ghosh et al, 2011;Umnajkitikorn et al, 2013;Yodpitak et al, 2013). The study results also clearly indicated that germination procedure increased the bioactivities of BR phytochemicals ( Figure 3A).…”
Section: Changes In the Bioactivity Of Black Ricementioning
confidence: 67%
See 1 more Smart Citation
“…Likewise, The α-glucosidase inhibiting property of phenolics, anthocyanins, GABA, and tocols was increased from 64.28 ± 2.51, 64.42 ± 2.70, 63.10 ± 1.71, and 63.62 ± 1.35 to 81.44 ± 2.05, 80.84 ± 2.23, 76.40 ± 2.01, and 76.59 ± 1.33% of inhibition/mg of extracts, respectively ( Figure 3A (b)). The germination improved the free radical scavenging ability of several Thai rice varieties (Daiponmak et al, 2010;Chutipaijit et al, 2009Chutipaijit et al, , 2011Ghosh et al, 2011;Umnajkitikorn et al, 2013;Yodpitak et al, 2013). The study results also clearly indicated that germination procedure increased the bioactivities of BR phytochemicals ( Figure 3A).…”
Section: Changes In the Bioactivity Of Black Ricementioning
confidence: 67%
“…Umnajkitikorn et al (2013) reported that the presence of salt (150 mM NaCl) enhanced the free radical scavenging ability of rice (cultivar Kum Doi Saket). Several studies reported the improvement of total phenolic, anthocyanins, and flavonoids content in Thai rice varieties during germination under the salinity (60-200 mM NaCl) (Chutipaijit et al, 2009(Chutipaijit et al, , 2011Daiponmak et al, 2010;Ghosh et al, 2011). The germination of cold sensitive rice seeds at 17 °C improved the antioxidant property of rice seedlings, especially lipid peroxidation, and superoxide dismutase activity, and further facilitated the accumulation of plant hormone gibberellic acid, which diminished the impact of cold stress (Grohs et al, 2016).…”
Section: Changes In the Phytochemical Content Of Gbr During Stress Comentioning
confidence: 99%
“…19 was found to contain cyaniding 3-glucoside, as suggested by OD 535 . It has been reported that the majority of black rice plants contain anthocyanidin-3-glucosides as the major anthocyanin, which functions as the major antioxidant compound [6,38,42,43] and strong superoxide radical scavenging activity [44,45,46]. Since Br no.…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive components in the rice bran extract were diff erent due to several factors, including cultivation techniques, ripening environments and growing conditions (11,12). All rice bran extracts had signifi cantly lower (p≤0.05) antioxidant activities than the corresponding positive controls.…”
Section: Total Anthocyanin Total Fl Avonoid and Total Phenolic Contentsmentioning
confidence: 99%
“…It was found in an in vitro study that Mn contributes to the antioxidant activity of rice (10). Concentrations of phenolics, fl avonoids, anthocyanins and minerals are diff erent depending on variety, growing conditions and soil components (11,12). Various cultivars of black glutinous rice are grown in the northern region of Thailand and they may have diff erent antioxidant components that need to be investigated.…”
Section: Introductionmentioning
confidence: 99%